Aristóteles e a justiça tributária contemporânea - Amorim, Roberto Soriano de (2008)
The purpose of this investigation is to create a reference in the interpretation of the argumentative discourse that intends to sustain the legitimacy of the national tax system. Thus, it is believed that, while highlighting the convincing terms, the understanding of the convincing process is made possible. In the form of a draft, the procedure aims at comparing the Aristotelian discourse as far as the meaning of the term justice is concerned, its support social living and its consequence equality converted, in our modern society, to the term contributive capacity , for the amendment to the modern rational juridical tax system . In order to reach this goal, preserved the drafting nature, it is highlighted in its originality (clearly, with the recognition of the fact that the interpretation of the old has a misleading factor because of the meaning of the values nowadays), the essential terms built in the Aristotelian theory happiness- justice virtue and equality). Because it is fundamental to build the theoretical model to make a description of the object of the tax analysis and its nature in the modern society according to its juridical configuration and also its sustaining, in the form of making tax fundaments legitimate, this means, tax justice. Finally in the form of preliminary studies (because this is the intention of this study), attempts to get closer and to differentiate between justice, Aristotelian and contemporary justice, this in the tax form. It is important to highlight that because the pretension is to identify the convincing resources, the exam of the economic - socio cultural and politic reality will not be done because this will be the objective of another step the authorizing methodological resource in the reading of the convincing rhetoric of the legal text, in the tax area, in modern society